Bridging the divide: The perceived efficacy of datalogging in fostering higher-order thinking and conceptual understanding in science practical’s - English, Vincent (International Journal of Educational Technology and Learning, 2025)
Practical work has long been positioned as central to school science, yet its effectiveness in promoting genuine conceptual understanding and higher-order thinking remains contested. This study investigates whether datalogging (probeware) can help bridge the persistent gap between “hands-on” activity and “minds-on” learning in science practicals. Drawing on Millar and two-domain model of practical work, the research explores science teachers’ perceptions of datalogging as a mediator between the domain of objects and observables and the domain of scientific ideas. Adopting a post-positivist stance and a large-scale cross-sectional survey design, an online questionnaire was distributed to 62,340 named science teachers across the UK, USA, Australia, Ireland, and New Zealand, yielding 2,126 valid responses. Exploratory factor analysis of 21 Likert-scale items identified two robust latent constructs: Datalogging as a Facilitator of inquiry, higher-order thinking, and conceptual understanding; and Teacher Apprehension, capturing concerns about reliability, setup time, and classroom management. Multiple regression analyses showed that positive perceptions of datalogging were strongly associated with greater proportions of hands-on practical time and specific subject specialisms, indicating that the pedagogical context strongly conditions the perceived efficacy of the technology. Teachers reported that datalogging particularly enhances students’ ability to interpret graphs, link observations to theory, and engage in open-ended, investigative work. At the same time, apprehension about technical complexity emerged as a non-trivial barrier to adoption. The study concludes that datalogging is perceived not as a marginal add-on but as a powerful cognitive mediator that can revitalise practical science—provided it is supported by sustained, pedagogically focused professional development and reliable classroom technology.